Comprensión lectora y rendimiento académico en alumnos de segundo grado de primaria de una institución educativa del Callao - Alva Castillo, Gloria Mariella (2012)
The research was to determine the correlation between reading comprehension and academic achievement in the areas of learning: communication, mathematical logic, personal social, environment and science and religion students in the second grade of a public school in Callao. The design was descriptive correlational. The sample consisted of 75 students of which 40 women and 35 men. The instrument used was the reading comprehension test of linguistic complexity Progressive (CLP) Alliende, Condemarín and Milicic (1993). Adapted by Ana Delgado 2004 to measure the academic performance of the notes were used to the official minutes of evaluation of each of areas. It was concluded that there is a significant correlation coefficient falls between reading comprehension and academic performance, both overall and in each of the areas assessed.